OP0228 Rituximab Monotherapy of Severe Hcv-Related Cryoglobulinemic Vasculitis for More than 2 Years: Follow-Up of A Randomized Controlled Multicentre Study. (10th June 2014) - Quartuccio, L.; Zuliani, F.; Corazza, L.; Scaini, P.; Zani, R.; Lenzi, M.; Tavoni, A.; Sebastiani, M.; Baldovino, S.; Urraro, T.; Saccardo, F.; Sbreglia, C.; et al.
Abstract : Background: Two independent controlled randomized trials demonstrated the efficacy and safety of rituximab (RTX) monotherapy in severe cryoglobulinemic vasculitis (CV) (1, 2), with one reporting a prolonged follow-up (1). Objectives: To report the very long term efficacy and safety of RTX monotherapy in severe CV since a regimen of RTX monotherapy was maintained after the end of the abovementioned trial (1). Methods: Long term follow up data of a trial of RTX in severe CV (1) were analysed. During this follow-up, only RTX monotherapy was used. Disease activity at the last follow-up visit, adverse events and survival were registered. Clinical response was evaluated at the last follow-up visit, and was scored as follows: i) complete remission (no activity), partial remission (response >50% of at least one manifestation among glomerulonephritis, severe neuropathy or skin ulcers) (1), and active disease. Results: After the end of the 2-year controlled trial (1), follow-up data were available in 36 patients undergoing RTX, all HCV positive. The mean follow up after the beginning of RTX therapy (1) was 70.22±20.41 months, including 29 patients followed for more than 4 years (78.4±12.6 months) and 7 patients followed for 2.4-4 years (36.4±6 months). Of them, 3 patients were lost from follow-up shortly after the end of the trial, and 9 patients died. Of the remaining 24 patients, 14/24 (58.3%) showed complete clinical remission at the last follow-up, 6/24 (25%) a partial remission, while 4/24 (16.7%) had an active disease. A first repeated RTX course (1 g two weeks apart) was required in 50% of the patients (12/24), while 25% of the patients (6/24) needed more than one course, for a total of 19 retreatments. Patients were retreated for nephritis (7/19), neuropathy (6/19), skin ulcers (7/19) or diffuse purpura (6/19). Three patients underwent a maintenance RTX regimen, all with 1 g × 2 every 6 months, with a complete and partial remission at the last follow-up noticed in 2/3 and 1/3, respectively. Recurrent infections occurred only in three patients (8%; urinary and upper respiratory), and they were related to persistent hypogammaglobulinemia in 2/3. Death occurred in 9 patients, all showing persistent active disease. Conclusions: A long-term RTX therapy lasting several years is effective and safe in about two thirds of the patients with severe CV. The advantage of retreatment at relapse regimen instead of a maintenance therapy, and whether this may occur in a further subset of patients, needs further investigation. References: De Vita S, et al. Arthritis Rheumatol. 2012;64(3):843-53. Sneller MC, et al. Arthritis Rheumatol. 2012;64(3):835-42. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3872